Is CSR the panacea for SMEs? A study of socially responsible SMEs during economic crisis. Issue 2 (April 2021) - Magrizos, Solon; Apospori, Eleni; Carrigan, Marylyn; Jones, Rosalind
Abstract: There is increasing research attention as to how SMEs might realize corporate social responsibility opportunities. Most studies focus on the pursuance of responsible business strategies that result in favourable business outcomes. This study investigates SMEs who actively participate in CSR activities in a south-eastern European country during the economic crisis of the Eurozone. Data collected reveals that stakeholder salience and proximity moderate the relationship between CSR and financial performance. The context of this study is important as it addresses the paucity of research carried out in countries during economic crisis and sheds light on the positive aspects of CSR practices adopted during crisis.